Análisis del comportamiento humano y control estratégico empresarial en la influencia del índice de accidentabilidad en obras de construcción - Leyva Vargas, Rafael Baltazar (2023)
ncidents occurred at work were analyzed; As of 2016, business strategic control was implemented and applied, the influence of the accident rate in this company was measured and the following question ¿was raised: In what way and to what extent do human behavior and business strategic control influence the accident rate?The application of business strategic control implemented in the construction company influenced the reduction of accident rates which were 20.78, 22.81, 19.99 for the years 2017, 2018 and 2019 respectively to an accident rate of 1.15 for the year 2020.